Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region - Jendek, Eduard; Grebennikov, Vasily V. (Zootaxa, 2019)
Twenty new species of Agrilus jewel beetles from the Oriental region are described and illustrated: Agrilus cicadelloides sp. nov. (Malaysia: Sarawak); A. draco sp. nov. (Malaysia: Sabah); A. hergovitsi sp. nov. (Malaysia: Johor); A. hik sp. nov.(Cambodia); A. ika sp. nov. (Solomon Islands); A. jankae sp. nov. (Indonesia: Sumatra, Singapore); A. jum sp. nov. (Laos); A. kon sp. nov. (Cambodia); A. mimicus sp. nov. (Laos); A. qom sp. nov. (Laos); A. titi sp. nov. (Malaysia: Perak); A. uxo sp. nov. (Vietnam); A. wos sp. nov. (Laos); A. xen sp. nov. (Laos); A. xia sp. nov. (Laos); A. xis sp. nov. (Laos); A. yoa sp. nov. (Laos, Vietnam); A. yuk sp. nov. (Laos); A. zao sp. nov. (Indonesia: Java and Sumba Islands); A. zim sp. nov. (Malaysia: Pahang).